Dynamics of the ferrofluid layer lying on a liquid substrate under the action of alternating magnetic fields - Khokhryakova(Bushueva), C.A.; Kostarev, K.G.; Lebedev, A.V.; Shmyrova, A.I.; Paravina, D.K. (Perm Federal Research Centre Journal, 2017)
Disintegration of the horizontal ferrofluid layer on a liquid substrate accompanied by the formation of an ordered drop system under the action of a uniform vertical magnetic field was investigated experimentally. The critical intensity of the magnetic field at which the layer decays toseparate drops depends on the layer thickness, the diameter of the cell and the magnetic susceptibility of the ferrofluid. It was shown that the number of drops, their size distribution and spatial period are determined by the velocity of the field intensity growth.The impact of a vertical oscillating magnetic field to the ferrofluid solid layer experimentally investigated. The length of concentric waves traveling on the surface of the layer depends on its thickness, the diameter of the cell and the field frequency. The action of alternating and constant vertical magnetic fields on the horizontal ferrofluid layer was studied experimentally. It has been found that the application of small oscillations has a stabilizing effect on the two-layer liquid system.